Antibacterial Effect of Selenium Hybrid Nanoparticles and Sea Cucumber Extract on E.coli, Micrococcus luteus and Bacillus Cereus - Mahnaz Mohammadi; Shirin Hafezi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd, 2023)
Introduction: Sea cucumber is one of the important aquatic animals that has many nutritional and medicinal properties and is of medical importance due to the presence of compounds with therapeutic and antibacterial effects. The purpose of this study was to investigate the antibacterial effect of selenium hybrid nanoparticles and sea cucumber extract on Escherichia coli, Micrococcus luteus and Bacillus cereus bacteria. Methods: MIC evaluation method was determined for the cytotoxic effect of sea cucumber extract on microbial cells. To carry out this research, after collecting and extracting sea cucumbers, the cytotoxicity of this extract on microbial cells was determined using the MIC method. Then, the antibacterial effect of sea cucumber extract, selenium hybrid nanoparticle and the combined effect of sea cucumber extract and selenium hybrid nanoparticle on Escherichia coli, Micrococcus luteus and Bacillus cereus bacteria were evaluated. Statistical analysis was done using SPSS version 16 software. Results: The results of the experiments showed that sea cucumber extract with different dilutions had an antibacterial effect on Escherichia coli bacteria, Micrococcus luteus and Bacillus cereus. These results also applied to the tests performed with selenium nanomedicine. Interestingly, after combining a certain amount of sea cucumber extract and selenium nanomedicine, a greater antibacterial effect was observed on the above-mentioned 3 bacteria. Conclusion: The synergistic effect of sea cucumber extract and selenium nanoparticles has a higher level of antibacterial properties.